Pengaruh Harga, Kualitas Produk, Lokasi, Dan Promosi Terhadap Keputusan Pembelian - M. Arief Ginanjar; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract  The purpose of this study was to determine the effect of price, product quality, location, and promotion on purchasing decisions at Kopi Siippp Malang Raya. The sample in this study was 50 employees. The technique used in data collection is in the form of a questionnaire or respondents are asked to fill out a list of questions. The methods used in this study include instrument testing (validity test, reliability test and normality test), classical assumption test (heteroscedasticity and multicollinearity test), multiple linear regression analysis and statistical tests (F test, t test, and R2). Hypothesis testing is done with the help of SPSS 16.0 The results of this study indicate that the variables of price, product quality, location, and promotion have a significant effect on purchasing decisions for Kopi Siippp Malang Raya. Keywords: Price, Product Quality, Location, Promotion, Purchase Decision